Sulfur-tolerant noble metal-based CO oxidation catalyst as well as preparation method and application thereof
By pre-reduction-induced activation preparation of the catalyst parent body, a specific surface-interface structure is formed, the problem of existing catalysts inactivation in sulfur-containing CO exhaust gas is solved, and an efficient and stable CO oxidation reaction is achieved, which is suitable for exhaust gas treatment in the petrochemical industry.
Patent Information
- Application Number
- CN202311165143.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-09-11
AI Technical Summary
The existing catalysts are inactivated in sulfur-containing CO exhaust gas, which is difficult to meet the demand for sulfur-resistant CO oxidation catalysts in the petrochemical industry.
Pre-reduction-induced activation of the catalyst parent body is prepared to form a specific surface-interface structure, which improves the catalyst's sulfur resistance. The catalyst consists of a support, active component (Pt and/or Pd) and additives (Fe, Co and Ni). The active component forms alloy particles with the additives and becomes a sulfur hybrid state after induced activation.
The CO conversion rate under high airspeed and high sulfur content is maintained at more than 99%, which significantly improves the sulfur resistance stability and activity of the catalyst, and is suitable for a variety of low-concentration CO removal conditions.
Smart Images

Figure CN119588375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon monoxide oxidation catalysts, and in particular to a sulfur-resistant noble metal-based CO oxidation catalyst and a preparation method and application thereof. Background Art
[0002] Carbon monoxide (CO) is a colorless, odorless, toxic gas that generally comes from incomplete combustion or partial oxidation of coal, gasoline and natural gas. CO has a strong binding force with hemoglobin and is therefore highly toxic. At higher concentrations, it can cause varying degrees of poisoning symptoms in people, harming the brain, heart, liver, kidney, lungs and other tissues of the human body, and even electric shock-like death. The minimum lethal concentration for human inhalation is 5000ppm (5 minutes). Therefore, in the production process of petrochemical products, strict requirements should be made for the emission content of CO in tail gas. With increasingly stringent environmental protection requirements, Beijing, Zibo and other regions have strictly restricted the CO concentration in the tail gas of chemical plants.
[0003] In some chemical production processes, the tail gas produced contains low concentrations of CO gas (<20000ppm) (such as the analytical gas and CO 2 Product gas, etc.), for this type of tail gas, the recovery cost is high. In order to meet the emission requirements, adsorption, photocatalysis, low-temperature plasma conversion, combustion and other methods are usually used to remove CO. Among them, the catalytic oxidation method introduces a high-efficiency catalyst on the basis of the combustion method to reduce the temperature of the combustion process. It has the advantages of simple process and high removal efficiency, and therefore has received widespread attention.
[0004] At present, there are many public reports on catalysts for low-concentration CO catalytic oxidation, usually using precious metals such as Pt and Au as active components. However, CO-containing waste gas from many chemical plants usually contains low concentrations of sulfides (<50ppm, including H 2 S, COS, etc.). Such sulfur-containing compounds have a strong poisoning effect on precious metal catalysts and easily lead to catalyst deactivation. Currently, there are few reports on sulfur-resistant carbon monoxide oxidation catalysts, and the few catalysts that can be used for sulfur-containing CO tail gas treatment usually require more stringent reaction conditions.
[0005] Patent application CN114210335A discloses the preparation and application of a low-temperature, water-resistant and sulfur-resistant non-precious metal catalyst for removing carbon monoxide. The catalyst is a perovskite-type transition metal oxide (general formula: La 1x Sr x CoO 3 ). The catalyst can achieve 01000mg Nm 3 SO 210000ppm carbon monoxide flue gas with 0.20vol.% water vapor at 120150℃ and 300030000h 1 Under the condition of H2O, the removal efficiency of carbon monoxide is stable at more than 80%, but it is not pointed out that the catalyst has 2 Activity and stability in the presence of other sulfur species such as S.
[0006] Patent application CN111659415A discloses a method for preparing a coupled nanocomposite noble metal catalyst on an activated alumina carrier. The catalyst uses activated alumina as a carrier and CeO 2 , Fe 3 O 4 、MnO 2 , CuO 2 The coupled metal oxide is a modification agent, and the Pd and Pt noble metals are active components. At 25°C, when the CO inlet concentration is 5000ppm and the H 2 S content 5ppm, air velocity 10000h -1 Under the condition of 50h reaction time, the CO removal rate is maintained at 100%. However, the catalyst composition is complex and the preparation method is relatively cumbersome. At the same time, the change of hydrogen sulfide during the reaction is not mentioned, and the life of the catalyst cannot be further speculated. The reported catalyst life is far from industrial application.
[0007] Therefore, in view of the characteristics of sulfur-containing species in CO tail gas of the petrochemical industry, the targeted development of CO oxidation catalysts with intrinsic sulfur resistance has become a difficult problem that needs to be solved urgently. Summary of the invention
[0008] The purpose of the present invention is to provide a sulfur-resistant noble metal-based CO oxidation catalyst and its preparation method and application for the treatment of tail gas containing low concentration CO in industrial production processes including coal chemical industry, in order to improve the catalytic stability of the catalyst in the presence of sulfide (hydrogen sulfide, etc.). The sulfur-resistant noble metal-based CO oxidation catalyst of the present invention is prepared by pre-reduction-induced activation of the catalyst matrix to form a specific surface-interface structure, so that the catalyst can realize the selective oxidation function of sulfur-containing species and obtain excellent sulfur-resistant reaction ability in the carbon monoxide oxidation reaction.
[0009] In order to achieve the above-mentioned objectives, the present invention provides, on one hand, a sulfur-resistant precious metal-based CO oxidation catalyst, which comprises a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is Pt and / or Pd, the auxiliary agent is at least one of Fe, Co and Ni, and the carrier is at least one of titanium dioxide, cerium dioxide, aluminum oxide and zirconium dioxide, wherein the active component and part of the auxiliary agent form alloy particles.
[0010] Preferably, the sulfur-resistant noble metal-based CO oxidation catalyst forms Pt / Pd-A / AO x / MO x Surface-interface structure, where Pt / Pd-A is an alloy particle of active component and additive, and is in a sulfur-hybridized state, AO x Oxide of additive metal, MO x As a carrier.
[0011] Preferably, based on the total weight of the sulfur-resistant noble metal-based CO oxidation catalyst, the loading amount of the active component in terms of metal element is 0.1-1 wt %, and the loading amount of the auxiliary agent in terms of metal element is 0.1-3 wt %.
[0012] A second aspect of the present invention provides a method for preparing a sulfur-resistant noble metal-based CO oxidation catalyst, comprising the following steps:
[0013] (1) impregnating the support into an aqueous solution containing a noble metal precursor and an auxiliary agent precursor, and then drying and calcining to obtain a catalyst precursor;
[0014] (2) subjecting the catalyst precursor to a pre-reduction treatment in a hydrogen-containing atmosphere to obtain a catalyst intermediate;
[0015] (3) the catalyst intermediate is reacted with CO and H 2 Induce activation in an atmosphere of S;
[0016] Among them, the noble metal is Pt and / or Pd, the carrier is at least one of titanium dioxide, cerium dioxide, aluminum oxide and zirconium dioxide, and the metal element in the auxiliary agent precursor is at least one of Fe, Co and Ni.
[0017] Preferably, in step (1), the impregnation process is equal volume impregnation.
[0018] Preferably, the impregnation process includes a stirring stage and a standing stage, the stirring stage lasts for 0.5-1 h, and the standing stage lasts for 6-18 h.
[0019] Preferably, in step (1), the carrier is calcined before impregnation.
[0020] Preferably, the calcination conditions of the carrier include: a temperature of 400-700° C. and a calcination time of 4-8 hours.
[0021] Preferably, the particle size of the carrier is 10-500 nm and the specific surface area is 60-200 m 2 / g.
[0022] Preferably, in step (1), the noble metal precursor is at least one of chloroplatinic acid, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
[0023] Preferably, in step (1), the auxiliary agent precursor is at least one of nitrates, chlorides and sulfates of auxiliary agent metals, more preferably nitrates of auxiliary agent metals.
[0024] Preferably, in step (1), during the drying process, the drying temperature is 60-90°C, and the drying time is 12-24h; during the roasting process, the roasting temperature is 400-600°C, the roasting time is 3-6h, and the heating rate is 1-3°C / min.
[0025] Preferably, in step (2), the hydrogen content in the atmosphere of the pre-reduction treatment is 5-50% by volume, preferably 5-10% by volume.
[0026] Preferably, the temperature of the pre-reduction treatment is 300-500°C.
[0027] Preferably, in step (3), the activation-inducing atmosphere contains CO, H 2 S and N 2 , wherein the content of CO is 2-5% by volume, and H 2 The content of S is 50-200ppm, N 2 The content is 95-98% by volume.
[0028] Preferably, the activation induction temperature is 200-350°C.
[0029] The present invention also provides a sulfur-resistant noble metal-based CO oxidation catalyst prepared by the above method.
[0030] The present invention also provides the use of the above sulfur-resistant noble metal-based CO oxidation catalyst as a catalyst for carbon monoxide oxidation reaction.
[0031] Preferably, the reaction raw gas used in the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
[0032] The technical solution of the present invention has the following advantages:
[0033] (1) Compared with other carbon monoxide oxidation catalysts, the sulfur-resistant noble metal-based CO oxidation catalyst of the present invention can achieve highly selective oxidation of hydrogen sulfide species to sulfur dioxide, reducing the adsorption and deposition of sulfur species on the catalyst;
[0034] (2) Compared with other carbon monoxide oxidation catalysts, the sulfur-resistant noble metal-based CO oxidation catalyst of the present invention has a high efficiency at a space velocity of 10000 h -1, reaction temperature 250°C, CO concentration of reaction raw gas 6000ppm and the presence of 50ppm hydrogen sulfide. After 200h reaction time, the CO conversion rate still remained above 99%.
[0035] The sulfur-resistant noble metal-based CO oxidation catalyst of the present invention has simple composition and preparation method, low preparation cost, good repeatability, is suitable for large-scale production, and has high activity and stability. Relying on the catalyst of the present invention, a low-concentration carbon monoxide catalytic removal technology can be formed, which is suitable for a variety of low-concentration carbon monoxide removal conditions including the presence of sulfides, and can reduce the carbon monoxide concentration in the tail gas to below 50ppm. It can be widely used in tail gas treatment in petrochemical, steel, industrial kilns, garbage incineration and other processes, and is of great significance for protecting the atmospheric environment and ensuring human health. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The catalyst PtFe / TiO in Example 1 2 A graph of catalytic oxidation CO conversion;
[0037] Figure 2 The catalyst PtFe / TiO in Example 1 2 TEM images of
[0038] Figure 3 The catalyst PtFe / TiO in Example 1 2 STEM-HAADF diagram of
[0039] Figure 4 The catalyst PtFe / TiO in Example 1 2 HRTEM images of
[0040] Figure 5 The catalyst Pt / Fe / TiO in Comparative Example 1 2 STEM-HAADF diagram of . DETAILED DESCRIPTION
[0041] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0042] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0043] Unless otherwise specified, the mass percentage of each component constituting the catalyst in the present application refers to the mass percentage of the corresponding component in the mass of the catalyst.
[0044] Unless otherwise specified, the content of each component in the gas composition used for catalyst pre-reduction and induced activation in this application refers to the volume percentage of the corresponding component in the total gas volume.
[0045] The sulfur-resistant noble metal-based CO oxidation catalyst of the present invention comprises a carrier and an active component and an auxiliary agent supported on the carrier. The active component is Pt and / or Pd. The auxiliary agent is at least one of Fe, Co and Ni. The carrier is at least one of titanium dioxide, cerium dioxide, aluminum oxide and zirconium dioxide.
[0046] In the catalyst described in the present invention, part of the auxiliary metal forms alloy particles with the precious metal Pt and / or Pd, and part of it exists in the form of oxide. Among them, Pt and / or Pd as active components form alloy particles with part of the auxiliary metal A, namely Pt / Pd-A alloy particles. The Pt / Pd-A alloy particles are highly dispersed in the catalyst, and become sulfur-hybridized alloy particles after induced activation. The average particle size of the Pt / Pd-A alloy particles can be 4-6nm.
[0047] In the catalyst of the present invention, in a preferred embodiment, the catalyst is prepared by volume impregnation-drying-calcination-prereduction-induced activation to form Pt / Pd-A alloy metal active particles, and to form Pt / Pd-A / AO x / MO x Surface-interface structure, where Pt / Pd-A is an alloy particle of active component and additive, and is in a sulfur-hybridized state, AO x Oxide of additive metal, MO x As a carrier.
[0048] In the catalyst described in the present invention, based on the total weight of the sulfur-resistant precious metal-based CO oxidation catalyst, the loading amount of the active component in terms of metal element is 0.1-1wt%, preferably 0.2-0.8wt%, and more preferably 0.3-0.6wt%; the loading amount of the auxiliary agent in terms of metal element is 0.1-3wt%, preferably 0.3-2wt%, and more preferably 0.8-1.5wt%.
[0049] The method for preparing the sulfur-resistant noble metal-based CO oxidation catalyst of the present invention comprises the following steps:
[0050] (1) impregnating the support into an aqueous solution containing a noble metal precursor and an auxiliary agent precursor, and then drying and calcining to obtain a catalyst precursor;
[0051] (2) subjecting the catalyst precursor to a pre-reduction treatment in a hydrogen-containing atmosphere to obtain a catalyst intermediate;
[0052] (3) the catalyst intermediate is reacted with CO and H 2 The activation was induced in an atmosphere of S.
[0053] In the method of the present invention, the carrier is at least one of titanium dioxide, cerium dioxide, aluminum oxide and zirconium dioxide. The particle size of the carrier can be 10-500nm, and the specific surface area can be 60-200m 2 In one embodiment, when the carrier is titanium dioxide, it is preferably anatase-type nano-titanium dioxide white powder with a purity of more than 99.9%, a particle size of 15-60 nm, and a specific surface area of 60-120 m 2 / g, the carrier has a large specific surface area and good hydrophilicity. In another embodiment, when the carrier is cerium dioxide, aluminum oxide or zirconium dioxide, its purity is preferably above 99.99%.
[0054] In the method of the present invention, the carrier is calcined before impregnation. The calcination conditions of the carrier may include: a temperature of 400-700° C. and a calcination time of 4-8 hours.
[0055] In the method of the present invention, the noble metal in the noble metal precursor is Pt and / or Pd. The noble metal precursor can be at least one of chloroplatinic acid, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate, preferably chloroplatinic acid and / or palladium nitrate.
[0056] In the method of the present invention, the metal element in the auxiliary agent precursor (ie, auxiliary agent metal A) is at least one of Fe, Co and Ni. The auxiliary agent precursor can be at least one of nitrate, chloride and sulfate of auxiliary agent metal, preferably nitrate of auxiliary agent metal.
[0057] In the method of the present invention, in step (1), the impregnation process is preferably equal volume impregnation. The specific operation process of the equal volume impregnation includes:
[0058] (I) The calcined carrier is subjected to a carrier saturated water absorption test. The specific method is: weigh a certain mass m 1 The carrier is placed in a measuring cylinder to obtain its dense volume V 1 ; Add a certain mass m 2 of deionized water, record its volume V 2 ; After sufficient stirring, let it stand for 12-24 hours, and then read the volume V of the mixed liquid in the measuring cylinder 3, the saturated water absorption rate ω of the sample is calculated by the following formula:
[0059]
[0060] (II) Calculating the weight of the noble metal precursor and the auxiliary agent precursor according to the mass of the carrier required for preparing the catalyst, dissolving the noble metal precursor and the auxiliary agent precursor materials calculated according to the loading amount of the noble metal (i.e., Pt and / or Pd) and the auxiliary agent metal A in deionized water, the volume of deionized water required for dissolution being obtained according to the saturated water absorption calculated according to the weight of the carrier for preparing the catalyst, and allowing the clarified precursor solution to stand for use;
[0061] (III) adding the calcined carrier to the prepared precursor solution, allowing the carrier to fully absorb the precursor solution, stirring for a period of time at room temperature to obtain a slurry mixture, and then letting it stand for a period of time.
[0062] Wherein, the impregnation process of step (III) includes a stirring stage and a standing stage, the stirring stage lasts for 0.5-1 h, and the standing stage lasts for 6-18 h.
[0063] In the method of the present invention, in step (1), during the drying process, the drying temperature is 60-90° C. and the drying time is 12-24 hours. The drying process can be carried out in a blast drying oven.
[0064] In the method of the present invention, in step (1), during the calcination process, the calcination temperature is 400-600° C., the calcination time is 3-6 hours, and the heating rate is 1-3° C. / min. The calcination process can be carried out in a muffle furnace.
[0065] In the method of the present invention, in step (2), the content of hydrogen in the atmosphere of the pre-reduction treatment is 5-50% by volume, preferably 5-20% by volume, and more preferably 5-10% by volume. In addition to hydrogen, other gases in the atmosphere of the pre-reduction treatment may be inert gases, such as argon.
[0066] In the method of the present invention, in step (2), the temperature of the pre-reduction treatment is 300-500° C. The time of the pre-reduction treatment can be 0.5-2 hours, preferably 1 hour.
[0067] In the method of the present invention, in step (3), during the induction activation process, the catalyst structure undergoes a directional change, and the H 2 The sulfur component is selectively oxidized to SO 2 , and as the induction time increases, SO 2The concentration gradually increases, and after a period of induction time, the sulfur concentration in and out of the reactor reaches equilibrium, and sulfur species will not continue to deposit on the catalyst. During the catalyst induction activation process, the CO oxidation reaction conversion rate is always maintained at more than 99%, so an intrinsic sulfur-resistant reaction can be achieved. Depending on the composition of the catalyst and the reaction induction gas, the induction period required from the start of reaction induction to the sulfur balance between the reactor inlet and outlet is different, and the induction time is 6-15h. In a preferred case, the induction activation atmosphere contains CO, H 2 S and N 2 , wherein the content of CO is 2-5% by volume, and H 2 The content of S is 50-200ppm, N 2 The content is 95-98% by volume.
[0068] In the method of the present invention, in step (3), the temperature for inducing activation is 200-350°C.
[0069] According to a specific embodiment of the present invention, the method for preparing the sulfur-resistant noble metal-based CO oxidation catalyst comprises:
[0070] S1, adding the calcined carrier to the prepared precursor solution (including the noble metal precursor and the auxiliary agent precursor), allowing the carrier to fully absorb the precursor solution, stirring and mixing at room temperature, and then standing to obtain a slurry mixture;
[0071] S2, placing the slurry mixture in a forced air drying oven for drying, and then placing it in a muffle furnace for calcination to obtain a catalyst matrix;
[0072] S3, placing the catalyst precursor in a flowing fixed bed reactor, first in H 2 / Ar mixed gas atmosphere, and then switch the gas to CO / H 2 S / N 2 Mixed gas, induction activation is carried out under the atmosphere of the mixer.
[0073] The present invention also provides a sulfur-resistant noble metal-based CO oxidation catalyst prepared by the above method. In the present invention, by pre-reducing and inducing activation of the catalyst matrix, a specific catalytic active site and surface-interface structure are formed, which can achieve H 2 The highly selective oxidation process of S species inhibits the adsorption and sulfate formation of S species and realizes H 2 High conversion rate oxidation reaction of carbon monoxide in the presence of sulfur.
[0074] The present invention also provides the use of the above-mentioned sulfur-resistant noble metal-based CO oxidation catalyst as a catalyst for carbon monoxide oxidation reaction. Specifically, the sulfur-resistant noble metal-based CO oxidation catalyst described in the present invention can be applied to a variety of low-concentration carbon monoxide removal conditions, especially a variety of low-concentration carbon monoxide removal conditions in the presence of sulfides. In a specific embodiment, the reaction raw gas used in the process of the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
[0075] Relying on the catalyst described in the present invention, a low-concentration carbon monoxide catalytic removal technology can be formed, which is suitable for a variety of low-concentration carbon monoxide removal conditions including the presence of sulfides, and can reduce the carbon monoxide concentration in the exhaust gas to below 50ppm. It can be widely used in exhaust gas treatment in petrochemical, steel, industrial kilns, waste incineration and other processes, and is of great significance for protecting the atmospheric environment and ensuring human health.
[0076] The following examples further illustrate the sulfur-resistant noble metal-based CO oxidation catalyst and its preparation method and application according to the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0077] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0078] Example 1
[0079] Intrinsically sulfur-resistant PtFe / TiO 2 Preparation of catalyst:
[0080] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then make up to 1L. After the solution is uniform and clear, let it stand for use.
[0081] The commercial anatase nano-titanium dioxide carrier (purity of more than 99.9%, particle size of 15-60nm, specific surface area of 60-120m 2 / g), placed in a muffle furnace, and calcined at 500°C in air atmosphere for 4 hours with a heating rate of 3°C / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0082] Saturated water absorption rate determination: weigh 1g of calcined TiO 2 The carrier was added to a 5 mL graduated cylinder and tapped on a flat surface. The dense volume was read as 1 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.3 mL. The TiO2 The saturated water absorption rate of the carrier is 0.7 mL / g.
[0083] Weigh 1.52g of the prepared chloroplatinic acid solution and mix with 1.16g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O) were added to a 50 mL beaker, and 6.3 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g of TiO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0084] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 4 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0085] The prepared catalyst matrix was placed in a fixed bed microreactor and first heated to 100 mL / min with 10 vol% H 2 The pre-reduction treatment was carried out at 500 °C for 1 h in a mixed gas atmosphere of 2 vol% CO / 0.005 vol% H 2 S / 97.995vol%N 2 Mixed gas was used for induction activation. During the induction process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered complete. The gas was then switched to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. 2 The reaction results of catalytic oxidation CO conversion rate are as follows Figure 1 As shown, from Figure 1 It can be seen that during the 200h long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate is maintained above 99%.
[0086] ICP-OES detection shows that the catalyst PtFe / TiO 2 In the present invention, based on the total weight, the content of Pt as a metal element is 0.41 wt %, and the content of Fe as a metal element is 1.20 wt %.
[0087] The PtFe / TiO 2 The transmission electron microscope (TEM) spectrum characterization of the catalyst obtained after the catalyst was induced and activated is shown in the figure below: Figure 2 shown.
[0088] The results of scanning transmission electron microscopy with high-angle annular dark field (STEM-HAADF) show that (see Figure 3 ), the catalyst PtFe / TiO 2 Pt and part of Fe exist in the form of Pt-Fe alloy particles, and the average particle size of the Pt-Fe alloy particles is about 5nm. After induced activation, the alloy particles are in a sulfur-hybridized state.
[0089] From the PtFe / TiO 2 High-resolution transmission electron microscopy (HRTEM) images of the catalyst (see Figure 4 ) It can be seen that after induced activation, a unique Pt-Fe / Fe 2 O 3 / TiO 2 The surface-interface structure is beneficial to improving the catalytic reaction activity and stability.
[0090] Example 2
[0091] Intrinsically sulfur-resistant PtCo / ZrO 2 Preparation of catalyst:
[0092] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then dilute to 1L. After the solution is uniform and clear, let it stand for use.
[0093] The nano zirconium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 500°C in air atmosphere for 4 hours at a heating rate of 3°C / min. After calcination, it was naturally cooled to room temperature and sealed for later use.
[0094] Determination of saturated water absorption: weigh 1g of calcined ZrO 2 The carrier was added to a 5 mL measuring cylinder and tapped on a flat surface. The dense volume was read as 0.65 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.3 mL. The ZrO 2 The saturated water absorption rate of the carrier is 0.35 mL / g.
[0095] Weigh 1.52g of the prepared chloroplatinic acid solution and mix with 1.16g of cobalt nitrate (Co(NO 3 )2 6H 2 O) were added to a 50 mL beaker, and 3.2 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g of ZrO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0096] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 4 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0097] The prepared catalyst matrix was placed in a fixed bed microreactor and first heated to 100 mL / min with 10 vol% H 2 The samples were pretreated at 500 °C for 1 h in a mixed gas atmosphere of 2.5 vol% CO / 0.01 vol% H 2 S / 97.49vol%N 2 Mixed gas was used for induction activation. During the induction activation process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered to be completed. The gas was then switched to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 14 hours. During the 200-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0098] ICP-OES detection shows that the catalyst PtCo / ZrO 2 In the embodiment, based on the total weight, the content of Pt as a metal element is 0.53 wt %, and the content of Co as a metal element is 1.97 wt %.
[0099] The results of scanning transmission electron microscopy with high-angle dark field (STEM-HAADF) show that the catalyst PtCo / ZrO 2The Pt and part of Co exist in the form of Pt-Co alloy particles, and the average particle size of the Pt-Co alloy particles is 6nm. After induced activation, the alloy particles are in a sulfur-hybridized state. High-resolution transmission electron microscopy characterization shows that Pt-Co / CoO is formed on the catalyst. x / ZrO 2 Surface-interface structure.
[0100] Example 3
[0101] Intrinsically sulfur-resistant PtNi / CeO 2 Preparation of catalyst:
[0102] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then make up to 1L. After the solution is uniform and clear, let it stand for use.
[0103] The nano-cerium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 500°C in air atmosphere for 4 hours with a heating rate of 3°C / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0104] Saturated water absorption rate determination: weigh 1g of calcined CeO 2 The carrier was added to a 5 mL measuring cylinder and tapped on a flat surface. The dense volume was read as 0.8 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.2 mL. The CeO 2 The saturated water absorption rate of the carrier is 0.6 mL / g.
[0105] Weigh 1.52g of the prepared chloroplatinic acid solution and mix with 1.16g of nickel nitrate (Ni(NO 3 ) 2 6H 2 O) were added to a 50 mL beaker, and 3.2 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g CeO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0106] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 500°C at a heating rate of 2°C / min, and calcined at 500°C for 4 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0107] The prepared catalyst precursor was placed in a fixed bed microreactor and first heated to 100 mL / min at 5 vol% H 2 The samples were pretreated at 500 °C for 1 h in a mixed gas atmosphere of 5 vol% CO / 0.02 vol% H 2 S / 94.98vol%N 2 Mixed gas was used for induction activation. During the induction activation process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered to be completed. The gas was then switched to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the balance of sulfur at the reactor inlet and outlet is 18 hours. During the 200-hour long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0108] ICP-OES detection shows that on the catalyst PtNi / CeO 2 In the embodiment, based on the total weight, the content of Pt as a metal element is 0.51 wt %, and the content of Ni as a metal element is 1.48 wt %.
[0109] The results of scanning transmission electron microscopy with high-angle dark field (STEM-HAADF) show that the catalyst PtNi / CeO 2 The Pt and part of the Ni exist in the form of Pt-Ni alloy particles, and the estimated particle size of the Pt-Ni alloy particles is 4nm. After induced activation, the alloy particles are in a sulfur-hybridized state. High-resolution transmission electron microscopy characterization shows that Pt-Ni / NiO is formed on the catalyst. x / CeO 2 Surface-interface structure.
[0110] Example 4
[0111] Intrinsically sulfur-resistant PtFe / TiO 2 Preparation of catalyst:
[0112] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then make up to 1L. After the solution is uniform and clear, let it stand for use.
[0113] The commercial anatase nano-titanium dioxide carrier (purity of more than 99.9%, particle size of 15-60nm, specific surface area of 60-120m 2 / g), placed in a muffle furnace, and calcined at 400°C in air atmosphere for 8 hours, with a heating rate of 1°C / min. After the calcination is completed, it is naturally cooled to room temperature and sealed for storage.
[0114] Saturated water absorption rate determination: weigh 1g of calcined TiO 2 The carrier was added to a 5 mL graduated cylinder and tapped on a flat surface. The dense volume was read as 1 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.3 mL. The TiO 2 The saturated water absorption rate of the carrier is 0.7 mL / g.
[0115] Weigh 1.19 g of the prepared chloroplatinic acid solution and mix with 0.77 g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O) were added to a 50 mL beaker, and 6.3 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g of TiO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0116] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 400°C at a heating rate of 1°C / min, and calcined at 400°C for 6 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0117] The prepared catalyst matrix was placed in a fixed bed microreactor and first heated to 100 mL / min with 10 vol% H 2 The pre-reduction treatment was carried out at 400 °C for 1 h in a mixed gas atmosphere of 2 vol% CO / 0.005 vol% H 2 S / 97.995vol%N 2 Mixed gas was used for induction activation. During the induction process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered complete. The gas was then switched to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. 2 The reaction results of catalytic oxidation CO conversion rate are as follows Figure 1 As shown, from Figure 1 It can be seen that during the 200h long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate is maintained above 99%.
[0118] ICP-OES detection shows that the catalyst PtFe / TiO 2 In the present invention, based on the total weight, the content of Pt as a metal element is 0.32 wt %, and the content of Fe as a metal element is 0.81 wt %.
[0119] The results of scanning transmission electron microscopy with high-angle dark field (STEM-HAADF) show that the catalyst PtFe / TiO 2 The Pt and part of the Fe exist in the form of Pt-Fe alloy particles, and the average particle size of the Pt-Fe alloy particles is about 5nm. After induced activation, the alloy particles are in a sulfur-hybridized state. Through high-resolution transmission electron microscopy characterization, it can be found that after induced activation, Pt-Fe / Fe 2 O 3 / TiO 2 Surface-interface structure.
[0120] Example 5
[0121] Intrinsically sulfur-resistant PtFe / TiO 2 Preparation of catalyst:
[0122] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then make up to 1L. After the solution is uniform and clear, let it stand for use.
[0123] The commercial anatase nano-titanium dioxide carrier (purity of more than 99.9%, particle size of 15-60nm, specific surface area of 60-120m 2 / g), placed in a muffle furnace, and calcined at 700℃ in air atmosphere for 4h, with a heating rate of 2℃ / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0124] Saturated water absorption rate determination: weigh 1g of calcined TiO 2 The carrier was added to a 5 mL graduated cylinder and tapped on a flat surface. The dense volume was read as 1 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.3 mL. The TiO 2The saturated water absorption rate of the carrier is 0.7 mL / g.
[0125] Weigh 2.19 g of the prepared chloroplatinic acid solution and mix with 1.45 g of ferric nitrate (Fe(NO 3 ) 3 9H 2 O) were added to a 50 mL beaker, and 6.3 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g of TiO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0126] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 600°C at a heating rate of 3°C / min, and calcined at 600°C for 3 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0127] The prepared catalyst matrix was placed in a fixed bed microreactor and first heated to 100 mL / min with 10 vol% H 2 / 90vol%Ar mixed gas atmosphere, 450℃ pre-reduction treatment for 1h. Then the gas was switched to 2vol%CO / 0.005vol%H 2 S / 97.995vol%N 2 Mixed gas was used for induction activation. During the induction process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered complete. The gas was then switched to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. 2 The reaction results of catalytic oxidation CO conversion rate are as follows Figure 1 As shown, from Figure 1 It can be seen that during the 200h long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate is maintained above 99%.
[0128] ICP-OES detection shows that the catalyst PtFe / TiO 2 In the embodiment, based on the total weight, the content of Pt as a metal element is 0.59 wt %, and the content of Fe as a metal element is 1.48 wt %.
[0129] The results of scanning transmission electron microscopy with high-angle dark field (STEM-HAADF) show that the catalyst PtFe / TiO 2 The Pt and part of the Fe exist in the form of Pt-Fe alloy particles, and the average particle size of the Pt-Fe alloy particles is about 5nm. After induced activation, the alloy particles are in a sulfur-hybridized state. Through high-resolution transmission electron microscopy characterization, it can be found that after induced activation, Pt-Fe / Fe 2 O 3 / TiO 2 Surface-interface structure.
[0130] Example 6
[0131] Intrinsically sulfur-resistant PtCo / ZrO 2 Preparation of catalyst:
[0132] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then dilute to 1L. After the solution is uniform and clear, let it stand for use.
[0133] The nano zirconium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 400°C in air atmosphere for 8 hours, with a heating rate of 1°C / min. After the calcination is completed, it is naturally cooled to room temperature and sealed for storage.
[0134] Determination of saturated water absorption: weigh 1g of calcined ZrO 2 The carrier was added to a 5 mL measuring cylinder and tapped on a flat surface. The dense volume was read as 0.65 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.3 mL. The ZrO 2 The saturated water absorption rate of the carrier is 0.35 mL / g.
[0135] Weigh 0.95g of the prepared chloroplatinic acid solution and mix with 0.73g of cobalt nitrate (Co(NO 3 ) 2 6H 2 O) were added to a 50 mL beaker, and 3.2 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g of ZrO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0136] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 400°C at a heating rate of 1°C / min, and calcined at 400°C for 6 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0137] The prepared catalyst matrix was placed in a fixed bed microreactor and first heated to 100 mL / min with 10 vol% H 2 The samples were pretreated at 400 °C for 1 h in a mixed gas atmosphere of 2.5 vol% CO / 0.01 vol% H 2 S / 97.49vol%N 2 Mixed gas was used for induction activation. During the induction activation process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered to be completed. The gas was then switched to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 14 hours. During the 200-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0138] ICP-OES detection shows that the catalyst PtCo / ZrO 2 In the embodiment, based on the total weight, the content of Pt as a metal element is 0.33 wt %, and the content of Co as a metal element is 1.67 wt %.
[0139] The results of scanning transmission electron microscopy with high-angle dark field (STEM-HAADF) show that the catalyst PtCo / ZrO 2 The Pt and part of Co exist in the form of Pt-Co alloy particles, and the average particle size of the Pt-Co alloy particles is 6nm. After induced activation, the alloy particles are in a sulfur-hybridized state. High-resolution transmission electron microscopy characterization shows that Pt-Co / CoO is formed on the catalyst. x / ZrO 2 Surface-interface structure.
[0140] Example 7
[0141] Intrinsically sulfur-resistant PtCo / ZrO 2 Preparation of catalyst:
[0142] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then dilute to 1L. After the solution is uniform and clear, let it stand for use.
[0143] The nano zirconium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 700℃ in air atmosphere for 4h, with a heating rate of 2℃ / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0144] Determination of saturated water absorption: weigh 1g of calcined ZrO 2 The carrier was added to a 5 mL measuring cylinder and tapped on a flat surface. The dense volume was read as 0.65 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.3 mL. The ZrO 2 The saturated water absorption rate of the carrier is 0.35 mL / g.
[0145] Weigh 1.29g of the prepared chloroplatinic acid solution and mix with 0.81g of cobalt nitrate (Co(NO 3 ) 2 6H 2 O) were added to a 50 mL beaker, and 3.2 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g of ZrO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0146] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 600°C at a heating rate of 3°C / min, and calcined at 600°C for 3 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0147] The prepared catalyst matrix was placed in a fixed bed microreactor and first heated to 100 mL / min with 10 vol% H 2 The mixture was pretreated at 450 °C for 1 h in a mixed gas atmosphere of 2.5 vol% CO / 0.01 vol% H 2 S / 97.49vol%N 2 Mixed gas was used for induction activation. During the induction activation process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered to be completed. The gas was then switched to 0.6 vol% CO / 0.005 vol% H2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the sulfur balance between the reactor inlet and outlet is 14 hours. During the 200-hour long-period carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0148] ICP-OES detection shows that the catalyst PtCo / ZrO 2 In the embodiment, based on the total weight, the content of Pt as a metal element is 0.45 wt %, and the content of Co as a metal element is 1.38 wt %.
[0149] The results of scanning transmission electron microscopy with high-angle dark field (STEM-HAADF) show that the catalyst PtCo / ZrO 2 The Pt and part of Co exist in the form of Pt-Co alloy particles, and the average particle size of the Pt-Co alloy particles is 6nm. After induced activation, the alloy particles are in a sulfur-hybridized state. High-resolution transmission electron microscopy characterization shows that Pt-Co / CoO is formed on the catalyst. x / ZrO 2 Surface-interface structure.
[0150] Example 8
[0151] Intrinsically sulfur-resistant PtNi / CeO 2 Preparation of catalyst:
[0152] Weigh 0.1 g of chloroplatinic acid (H 2 PtCl 6 ) into a 1L constant volume bottle, add deionized water to fully dissolve, and then dilute to 1L. After the solution is uniform and clear, let it stand for use.
[0153] The nano-cerium dioxide carrier (particle size of 10-500nm, specific surface area of 60-200m2) purchased from Sinopharm Chemical Reagent Co., Ltd. 2 / g), placed in a muffle furnace, and calcined at 600°C in air atmosphere for 3 hours at a heating rate of 2°C / min. After calcination, it was naturally cooled to room temperature and sealed for future use.
[0154] Saturated water absorption rate determination: weigh 1g of calcined CeO 2The carrier was added to a 5 mL measuring cylinder and tapped on a flat surface. The dense volume was read as 0.8 mL. After adding 2 mL of water, the mixture was stirred thoroughly and allowed to stand for 12 h. The volume of the mixed solution was read as 2.2 mL. The CeO 2 The saturated water absorption rate of the carrier is 0.6 mL / g.
[0155] Weigh 1.25g of the prepared chloroplatinic acid solution and mix with 0.98g of nickel nitrate (Ni(NO 3 ) 2 6H 2 O) were added to a 50 mL beaker, and 3.2 mL of deionized water was added and stirred thoroughly to dissolve. Subsequently, 10 g CeO 2 The carrier was stirred at room temperature for 0.5 h to obtain a slurry mixture. The beaker containing the mixture was sealed with a sealing film and placed in a cool and dry place for 12 h.
[0156] The slurry catalyst was placed in a crucible, placed in a muffle furnace in an air atmosphere, heated from room temperature to 600°C at a heating rate of 3°C / min, and calcined at 600°C for 3 hours. After calcination, the slurry catalyst was naturally cooled to room temperature, taken out and sealed for storage.
[0157] The prepared catalyst precursor was placed in a fixed bed microreactor and first heated to 100 mL / min at 5 vol% H 2 The mixture was pretreated at 480 °C for 1 h in a mixed gas atmosphere of 5 vol% CO / 0.02 vol% H 2 S / 94.98vol%N 2 Mixed gas was used for induction activation. During the induction activation process, the sulfide content in the tail gas at the reactor outlet was analyzed by gas chromatograph. When the sulfide content in the tail gas was the same as the sulfur content in the induction gas, the induction activation was considered to be completed. The gas was then switched to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The gas was subjected to carbon monoxide oxidation reaction evaluation. The reaction temperature was set at 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The reaction results show that the induction period from the start of induction activation to the balance of sulfur at the reactor inlet and outlet is 18 hours. During the 200-hour long-cycle carbon monoxide oxidation reaction, the carbon monoxide conversion rate was maintained at more than 99%.
[0158] ICP-OES detection shows that on the catalyst PtNi / CeO 2In the embodiment of the present invention, based on the total weight, the content of Pt as a metal element is 0.42 wt %, and the content of Ni as a metal element is 1.25 wt %.
[0159] The results of scanning transmission electron microscopy with high-angle dark field (STEM-HAADF) show that the catalyst PtNi / CeO 2 The Pt and part of the Ni exist in the form of Pt-Ni alloy particles, and the estimated particle size of the Pt-Ni alloy particles is 4nm. After induced activation, the alloy particles are in a sulfur-hybridized state. High-resolution transmission electron microscopy characterization shows that Pt-Ni / NiO is formed on the catalyst. x / CeO 2 Surface-interface structure.
[0160] Comparative Examples 1-3
[0161] The preparation methods of Comparative Examples 1, 2, and 3 correspond to those of Examples 1, 2, and 3, respectively, but the difference is that in the catalyst preparation process of Comparative Examples 1-3, the steps of pre-reduction treatment and induction activation are eliminated, and the calcined catalyst matrix is directly heated to 0.6 vol% CO / 0.005 vol% H 2 S / 5vol%O 2 / CO 2 The carbon monoxide oxidation reaction was evaluated in the gas. The reaction temperature was set to 250°C and the reaction space velocity was 10000h -1 The CO concentration and sulfide content at the reactor outlet were detected by gas chromatography. The activity and stability of each example and comparative example are shown in Table 1.
[0162] High-resolution transmission electron microscopy (HRTEM) showed that the catalysts prepared in Comparative Examples 1-3 did not contain sulfur-hybridized alloy particles and PtA / AO x / MO x Surface-interface structure. Taking the catalyst prepared in Comparative Example 1 as an example, the characterization results of the catalyst using a high-foot annular dark field scanning transmission electron microscope (STEM-HAADF) are as follows: Figure 5 As shown, from Figure 5 It can be seen that the platinum species on the catalyst exist in the form of individual particles and do not form a sulfur-hybridized alloy structure phase.
[0163] The comparison of the reaction activity evaluation of Examples 1-8 and Comparative Examples 1-3 is shown in Table 1, wherein T50 and T90 refer to the lowest temperatures at which the conversion rate reaches 50% and 90%, respectively.
[0164] Table 1
[0165]
[0166]
[0167] It can be seen from the results of the above examples and comparative examples that the catalyst activity and stability of the sulfur-resistant noble metal-based CO oxidation catalyst prepared by the method of the present invention are significantly better than those of the catalyst prepared in the comparative example. This shows that in the catalyst preparation process, the combination of pre-reduction and induced activation can promote the formation of a special catalyst structure, which has a promoting effect on the catalyst reaction activity and sulfur-resistant reaction stability.
[0168] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A sulfur-resistant noble metal-based CO oxidation catalyst, characterized in that: The invention comprises a carrier and an active component and an auxiliary agent supported on the carrier, wherein the active component is Pt and / or Pd, the auxiliary agent is at least one of Fe, Co and Ni, and the carrier is at least one of titanium dioxide, cerium dioxide, aluminum oxide and zirconium dioxide, wherein the active component and part of the auxiliary agent form alloy particles.
2. The sulfur-resistant noble metal-based CO oxidation catalyst according to claim 1, characterized in that: The sulfur-resistant noble metal-based CO oxidation catalyst forms Pt / Pd-A / AO x / MO x Surface-interface structure, where Pt / Pd-A is an alloy particle of active component and additive, and is in a sulfur-hybridized state, AO x Oxide of additive metal, MO x As a carrier.
3. The sulfur-resistant noble metal-based CO oxidation catalyst according to claim 1 or 2, characterized in that: Based on the total weight of the sulfur-resistant noble metal-based CO oxidation catalyst, the loading amount of the active component in terms of metal element is 0.1-1wt%, and the loading amount of the auxiliary agent in terms of metal element is 0.1-3wt%.
4. A method for preparing a sulfur-resistant noble metal-based CO oxidation catalyst, characterized in that: The method comprises the following steps: (1) impregnating the support into an aqueous solution containing a noble metal precursor and an auxiliary agent precursor, and then drying and calcining to obtain a catalyst precursor; (2) subjecting the catalyst precursor to a pre-reduction treatment in a hydrogen-containing atmosphere to obtain a catalyst intermediate; (3) inducing activation of the catalyst intermediate in an atmosphere containing CO and H2S; Among them, the noble metal is Pt and / or Pd, the carrier is at least one of titanium dioxide, cerium dioxide, aluminum oxide and zirconium dioxide, and the metal element in the auxiliary agent precursor is at least one of Fe, Co and Ni.
5. The method according to claim 4, characterized in that In step (1), the impregnation process is equal volume impregnation.
6. The method according to claim 5, characterized in that The impregnation process includes a stirring stage and a standing stage. The stirring stage lasts for 0.5-1 h, and the standing stage lasts for 6-18 h.
7. The method according to any one of claims 4 to 6, characterized in that: In step (1), the support is calcined before impregnation; Preferably, the calcination conditions of the carrier include: temperature of 400-700°C, calcination time of 4-8h; Preferably, the particle size of the carrier is 10-500 nm and the specific surface area is 60-200 m 2 / g.
8. The method according to any one of claims 4 to 6, characterized in that: In step (1), the noble metal precursor is at least one of chloroplatinic acid, platinum chloride, platinum nitrate, platinum acetylacetonate, palladium chloride, palladium nitrate and palladium acetate.
9. The method according to any one of claims 4 to 6, characterized in that: In step (1), the auxiliary agent precursor is at least one of nitrates, chlorides and sulfates of auxiliary agent metals, preferably nitrates of auxiliary agent metals.
10. The method according to any one of claims 4 to 6, characterized in that: In step (1), during the drying process, the drying temperature is 60-90°C and the drying time is 12-24h; during the roasting process, the roasting temperature is 400-600°C, the roasting time is 3-6h, and the heating rate is 1-3°C / min.
11. The method according to claim 4, characterized in that In step (2), the hydrogen content in the atmosphere of the pre-reduction treatment is 5-50% by volume, preferably 5-10% by volume; Preferably, the temperature of the pre-reduction treatment is 300-500°C.
12. The method according to claim 4, characterized in that In step (3), the activation-inducing atmosphere contains CO, H2S and N2, wherein the content of CO is 2-5% by volume, the content of H2S is 50-200 ppm, and the content of N2 is 95-98% by volume; Preferably, the activation induction temperature is 200-350°C.
13. A sulfur-resistant noble metal-based CO oxidation catalyst prepared by the method according to any one of claims 4 to 12.
14. Use of the sulfur-resistant noble metal-based CO oxidation catalyst according to any one of claims 1 to 3 or 13 as a catalyst for carbon monoxide oxidation reaction.
15. The use according to claim 14, characterized in that: The reaction raw gas used in the carbon monoxide oxidation reaction contains sulfides below 50 ppm.
Citation Information
Patent Citations
Palladium chloride-cupric chloride catalyst applied to normal-temperature catalytic oxidation of carbon monoxide and preparation
CN104014353A
Sulfur-tolerant volatile organic compound combustion catalyst and preparation method and application thereof
CN112871164A
PtCo / Co3O4-x-Al2O3 multi-interface structure catalyst as well as preparation method and application thereof
CN114308063A
Cited By
Low-precious metal CO oxidation sulfur-tolerant catalyst and preparation method and application thereof
CN121060512A
Sulfur-resistant moisture-proof CO oxidation regular-structure catalyst as well as preparation method and application thereof
CN121551025A
A sulfur-resistant and moisture-resistant CO oxidation regular structure catalyst, a preparation method and application thereof
CN121551025B
Composite SCO catalyst and preparation method thereof
CN121755184A